Food, gender, and diet quality: Regional experiences, evidence, and reflections - Lizarazo, Miguel; Ramos, Gresia; Jimenez, Daniel; Arce, Daniela (2025)
This document summarizes regional experiences related to food systems, gender, and diet quality, as shared during a series of webinars held from October 21 to 24, 2025. The discussions primarily focused on Guatemala, followed by Colombia, and brought together academic institutions and research organizations to reflect on evidence, methodologies, and lessons learned across different contexts.